Cotton Yield and Canopy Closure in North Carolina as Influenced by Row Width, Plant Population, and Leaf Morphology. Issue 4 (1st July 2013) - Riar, Ranjit; Wells, Randy; Edmisten, Keith; Jordan, David; Bacheler, Jack
ABSTRACT: Cotton ( Gossypium hirsutum L.) yield is partly determined by crop geometry, which is a function of row width and plant population. Field experiments were conducted in North Carolina during 2007 and 2008 to test the hypothesis that row width will be the determining factor in attaining canopy closure and hence greater fiber yield in North Carolina. The influences of both plant population and leaf morphology on the row width effects were also examined. Okra‐leaf (FiberMax 800 BR) and normal‐leaf (FiberMax 960 BR) cultivars were planted at 38‐ and 97‐cm row widths at populations of 7, 12, and 18 plants m −2 . Cotton grown at 38‐cm row width yielded more than cotton grown at 97‐cm rows in some but not all environments. The percentage of canopy closure and the percentage of photosynthetically active radiation interception showed a close relationship over row width, leaf morphology, plant population, and environment ( r 2 = 0.84, P < 0.001). Higher plant population increased light interception and canopy closure early in the season. However, with time, these differences were reduced and were absent by the last observations. Row width was an important cause of greater canopy closure but this did not consistently translate into yield differences and yields were more closely affected by cumulative rainfall. Economic analysis found no loss of profit in the lowest plant population in either row width indicating that seed costs could be reduced without decreasing yield.